Study on the Electrical Injection Regeneration of Industrialized B-Doped Czochralski Silicon PERC Solar Cells - Jiaxing Ye; Bin Ai; Jingsheng Jin; Depeng Qiu; Runxiong Liang; Hui Shen (International Journal of Photoenergy)
In this paper, 156 mm×156 mm boron-doped Czochralski silicon (Cz-Si) wafers were fabricated into PERC solar cells by using the industrial standard process; then, the as-prepared PERC solar cells were treated by the regeneration process using electrical injection and heating and the effects of different regeneration processes (temperature, time, and injection current) on the anti-light-induced degradation (anti-LID) performance of the PERC solar cells were investigated. The results show that under the condition of 10 A injection current and 30 min processing time, the optimal processing temperature is about 180°C for PERC solar cells to obtain the best anti-LID performance. Under the conditions of a temperature of 180°C, an injection current of 10 A, and a processing time of 0-30 min, the anti-LID performance of the PERC solar cells is enhanced with the increase in the processing time. When the processing time is 20 and 30 min, the efficiency, the short-circuit current, and the open-circuit voltage of the processed PERC solar cells are slightly higher than the initial values before the regeneration and remain stable in the subsequent 12-hour light degradation process at 45°C and 1-sun illumination. At a temperature of 180°C and a processing time of 30 min, the injection current of 6 A is enough to obtain a good regeneration effect, but the optimal injection current is around 10 A.